Analysis of Islamic Education Learning Planning Based on Religious Moderation in Indonesian State Islamic Religious Universities - Karliana Indrawari; Bakti Komlasari; Weni Sasmita; Erik Wiranata (At-Ta'lim : Media Informasi Pendidikan Islam, 2024)
ENGLISH: Analysis of Islamic Education Learning Planning Based on Religious Moderation in Indonesian State Islamic Religious UniversitiesObjective: This study aims to provide constructive input to educators at IAIN Curup, Bengkulu, Indonesia, in developing learning strategies that are more effective and follow the principles of religious moderation. Methods: This type of research uses a qualitative approach with a field study method. This research was conducted in 2023. The research subjects were lecturers, Deans, Heads of Islamic Education Study Programs, and students. Observation, interview, and documentation were used in data collection. Data analysis includes data review, data reduction, and data conclusion. Results: Learning planning in the Islamic Education Study Program at IAIN Curup focuses on religious moderation by integrating varied learning methods and considering the local context. Conclusion: The Islamic Education Study Program at IAIN Curup emphasizes religious moderation as a major component of its learning strategy. Students are taught to understand and apply the values of moderation in their daily lives through holistic approaches. Contribution: The research contributes as a guide for lecturers and a reference for the government and educational institutions in formulating Islamic education policies based on religious moderation.INDONESIAN: Analisis Perencanaan Pembelajaran Pendidikan Agama Islam Berbasis Moderasi Beragama di Perguruan Tinggi Keagamaan Islam Negeri IndonesiaTujuan: Penelitian ini bertujuan untuk memberikan masukan yang konstruktif kepada para pendidik di lingkungan IAIN Curup, Bengkulu, Indonesia dalam menyusun strategi pembelajaran yang lebih efektif dan sesuai dengan prinsip-prinsip moderasi beragama. Metode: Jenis penelitian menggunakan pendekatan kualitatif dengan metode studi lapangan. Penelitian ini dilaksanakan pada tahun 2024. Subyek penelitian yaitu Dosen, Dekan, Ketua Program Studi Pendidikan Agama Islam dan Mahasiswa. Observasi, Wawancara dan Dokumentasi dugunakan dalam pengumpulan data. Analisis data meliputi pengajian data, reduksi data dan kesimpulan data. Hasil: perencanaan pembelajaran di Program Studi Pendidikan Agama Islam di IAIN Curup menitikberatkan pada moderasi beragama melalui integrasi metode pembelajaran yang variatif, serta mempertimbangkan konteks lokal. Kesimpulan: Program Studi Pendidikan Agama Islam di IAIN Curup menekankan moderasi beragama sebagai komponen utama dari strategi pembelajarannya. Mahasiswa diajarkan untuk memahami dan menerapkan nilai-nilai moderasi dalam kehidupan sehari-hari melalui pendekatan holistik. Kontribusi: penelitian berkontribusi sebagai panduan bagi dosen dan referensi bagi pemerintah dan lembaga pendidikan dalam menyusun kebijakan pendidikan Islam berbasis moderasi beragama.